Computational quantum chemistry : insights into polymerization reactions - Soroush, Masoud (Elsevier, 2018)
Computational Quantum Chemistry: Insights into Polymerization Reactions consolidates extensive research results, couples them with computational quantum chemistry (CQC) methods applicable to polymerization reactions, and presents those results systematically. CQC has advanced polymer reaction engineering considerably for the past two decades. The book puts these advances into perspective. It also allows you to access the most up-to-date research and CQC methods applicable to polymerization reactions in a single volume. The content is rigorous yet accessible to graduate students as well as researchers who need a reference of state-of-the-art CQC methods with polymerization applications.